PERSEPSI MASYARAKAT TERHADAP CITRA POLISI LALU LINTAS DI POLSEK KECAMATAN TAMPAN KOTA PEKANBARU - Wardani, Vania Avissa; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
There were many phenomenons that deserved to be researched, one of thephenomenons was a bribe exploits in arresting every vehicles. That was certainly givinga positive and negative effect for the traffic warden image that was not ready been adiscipline in a rule of law equity yet.To know the result of this research, that is the reason why the researcher appliedthe collecting data technique by applying the observation technique and interviewingthe respondents. There was a way by assuming the sample or the respondents treatedwith the Accidental Sample Technique, which was a stipulation by the respondentstreated so spontaneously by people as bikers that interviewed on highway directly. Therespondents amounted to 36 persons. The researcher has totalled the deduction of 36persons based on the level of final data when the rejoinder was almost being homogenyand the researcher satisfied to expect the information. The kind of this research used bythe researcher here is the descriptive quantitative research.The result of this research indicated that it was sealed for the bribe exploits inarresting many vehicles were actually happened. So that the people perception for thetraffic warden image became a negative thing, moreover a few people were perceptivein a positive thinking. It could be seen with the perception factors, such as the individualexperience, the people experience, an interesting and a particular attention from thesocieties.The result of this research is expected to point out a general description for thereaders to collect the information about The People Perception for the Traffic WardenImage in the Sector Police of Tampan Pekanbaru.Keywords: Perception, Society, The Traffic Warden Image